Gut-Derived Metabolite Phenylacetylglutamine and White Matter Hyperintensities in Patients With Acute Ischemic Stroke - Yu, Fang; Feng, Xianjing; Li, Xi; Luo, Yunfang; Wei, Minping; Zhao, Tingting; Xia, Jian (Frontiers in Aging Neuroscience, 2021)
Background: White matter hyperintensity (WMH) burden is associated with a higher risk of ischemic stroke. Phenylacetylglutamine (PAGln) is a gut microbiota-derived metabolite that may induce cardiovascular events by activating platelets and increasing the risk of thrombosis. The relationship between plasma PAGln and WMH burden in patients with ischemic stroke is unknown. This study was designed to investigate the association between plasma PAGln and WMH burden in patients with acute ischemic stroke. Methods: A total of 595 patients with acute ischemic stroke were enrolled in this study within 14 days of symptom onset. The burden of WMH was evaluated using the Fazekas scale based on the fluid-attenuated inversion recovery sequence. The severity of overall WMH was defined as none–mild WMH (total Fazekas score 0–2) or moderate–severe WMH (total Fazekas score 3–6). Based on the severity of periventricular WMH (P-WMH) and deep WMH (D-WMH), patients were categorized into either a none–mild (Fazekas score 0–1) group or a moderate–severe (Fazekas score 2–3) group. Plasma PAGln levels were quantified using liquid chromatography–mass spectrometry. Results: We found that patients with moderate–severe overall WMH showed higher plasma PAGln levels than patients with none–mild overall WMH, and similar results were found in the analyses according to P-WMH and D-WMH. The logistic regression analysis showed that the fourth PAGln quartile was independently associated with moderate–severe overall WMH (adjusted 95% CI 1.134–4.018) and P-WMH (adjusted 95% CI 1.174–4.226). Conclusion: These findings suggest that higher plasma PAGln levels are associated with moderate–severe overall WMH and P-WMH in patients with acute ischemic stroke.